Reading trends and perceptions towards Islamic English websites as teaching materials - Zurina, Khairuddin; Azimah Shurfa, Mohammed Shukry; Nurshafawati, Ahmad Sani (Canadian Center of Science and Education, 2014)
This paper is a study of the reading trends and perceptions of Muslim Malaysian undergraduate students towards Islamic English websites as pedagogical materials in English language classrooms. Data was collected through a set of questionnaires to 180 students from the International Islamic University Malaysia (IIUM) and Universiti Sultan Zainal Abidin (UniSZA). The findings revealed that the students were self-motivated to read the materials to gain spiritual knowledge and to use the knowledge to deal with personal challenges. It also shows that the students recommend that the materials are used for pedagogical purposes in the learning of the English language. The study proposed that texts that bring enjoyment, inspiration, spiritual knowledge and personal development are used as reading materials in English lessons for Muslim students. This would enhance the motivation to read more whilst improving the proficiency of the English language.